HUBUNGAN ANTARA LINGKAR PINGGANG DENGAN KADAR GULA DARAH SEWAKTU PADA PENGUNJUNG LAPANGAN RENON PADA TAHUN 2018 - Michael Ferdinand; AA. Wiradewi Lestari; Sianny Herawati (Universitas Udayana, 2020)
Obesity can be construed as hoarding excess fat that raises the risk for health. The number of sufferers of obesity is increasing rapidly lately in urban areas in countries of low and medium income countries. One of the most important energy source is blood sugar. Blood sugar can be known with random blood sugar test or fasting blood sugar test. The work of insulin on body will decrease if body fat increase and body mass decrease. In obesity, insulin resistance one of which is caused by an inflammatory reaction. So as a result the glucose levels in the blood will increase. Metabolic disorders can occur when blood glucose levels both fasting blood sugar or random blood sugar increased and insulin work decreased. The purpose of this research is to know the association between random blood sugar levels with obesity at the Lapangan Puputan Renon visitors in the 2018. This research is analytic research in Lapangan Puputan Renon, Denpasar. The data was processed using the SPSS program. The data retrieved is the waist circumference to assess obesity and random blood sugar levels to assess diabetes mellitus. Random blood glucose data not distribute normally while waist circumference normally distribute. The male-sex respondents is 66.7%, while women 33.3%. Data on high blood sugar levels is 43.3%, whereas the normal 56.7%. A large waist circumference data 63.3% and 36.7% of normal. The results of this research state that the waist circumference with random blood sugar levels on Lapangan Puputan Renon visitors in September 2018 has a significant association with r=0.422; p=0.02. Keywords: Obesity, Diabetes Mellitus, Waist Circumference, Random Blood Sugar Levels.